Characterization of the protein kinase activity of avian sarcoma virus src gene product. - Maness, P F (1979)
The avian sarcoma virus src gene product, p60src, has been purified 650-fold from cytoplasmic extracts of the rat tumor cell line RR1022 by using ammonium sulfate fractionation, hydrophobic chromatography on omega-aminohexyl agarose, and ion exchange chromatography on phosphocellulose. Partially purified p60src is a monomer, with a native molecular weight of about 60,000 and an apparent pI of 6.0. In immunoprecipitates, p60src catalyzed phosphorylation of anti-p60src IgG heavy chains within the variable (VH) domain, which contains the heavy chain portion of the antigen combining site. Crude preparations of p60src contained phosphatase activity able to cleave phosphate from IgG heavy chains; this activity was removed by the purification procedure, and partially purified p60src could phosphorylate the heavy chain of specific antibody in solution. Furthermore, purified p60src catalyzed phosphorylation in solution of the general protein kinase substrate, alpha-casein, strengthening the hypothesis that it may in fact function as a protein kinase in vivo.